Gaya Bahasa dalam Novel Bidadari Berbisik Oleh Asma Nadia - Hanafi, Rizka; Rahayu, Sri (UIR PRESS, 2023)
The purpose of this study is to describe, analyze, and interpret in detail so that you can get a true reflection of the comparative language style and meaning in the Whispering Angel novel. This research method is descriptive method. This research uses a qualitative approach. The data source for this research is the novel Whispering Angel by Asma Nadia in 2020. This type of research is library research. The data collection method of this research is documentation and hermeneutic methods. The information studied was documented by reading, noting, and drawing conclusions and classified according to the type according to the theory used. The language styles in the novel Whispering Angel by Asma Nadia include comparative language styles: metaphor, hyperbole, smile, personification, anatonomasia, epithet, tropen, periphrasis, euphemism, synesthesia, dysphemism, allusion and metonomia. The style of language in the novel Whispering Angel by Asma Nadia is reflected in the choice of words as a factor of beauty, so that the reader can illustrate what the characters are experiencing in the novel. There are several meanings in the novel Whispering Angel by Asma Nadia, including: denotative and connotative meanings.